At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

-3x + 3y =3
-5x + y =13 Solve as a whole number


Sagot :

Answer:

X = 3 x − 14

y = − x + 5

Step-by-step explanation:

Solve for the first variable, then substitute the result into the other equation.

Esther

Answer:

x = -3, y = -2

(-3, -2)

Step-by-step explanation:

-3x + 3y = 3

-5x + y = 13

-5x + y = 13

+5x    +5x

y = 5x + 13

-3x + 3(5x + 13) = 3

-3x + 15x + 39 = 3

12x + 39 = 3

     - 39   -39

12x = -36

/12    /12

x = -3

Now, we solve for y:

-5x + y = 13

-5(-3) + y = 13

15 + y = 13

-15      -15

y = -2

(x, y) -> (-3, -2)

Hope this helps!

View image Esther